PsycEXTRA Dataset 2012
DOI: 10.1037/e651522012-001
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination and Perceived Stress in Sexual and Gender Minorities: Self-Esteem As a Moderating Factor

Abstract: Sexual and gender minorities are subjected to discrimination and stigmatization which increase vulnerability to psychological co-morbidities (Mays & Cochran, 2001). The mechanisms through which discrimination contributes to distress in lesbian, gay, bisexual and transgender (lgbt) communities can be partially elucidated through the minority stress model. The minority stress model argues that minorities are subjected to negative societal attitudes and discrimination that results in excessive psychosocial stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 118 publications
0
3
0
Order By: Relevance
“…The mediating effect of self-esteem in the relation between perceived discrimination and suicidal ideation can be explained by recognizing the importance of the looking-glass self. Wike (2014) noted that self-esteem relates closely with identity development and self-concept, in which the importance of the looking-glass self has been highlighted. The looking-glass self is where one imagines how others regard and judge them, directly influencing their selffeelings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mediating effect of self-esteem in the relation between perceived discrimination and suicidal ideation can be explained by recognizing the importance of the looking-glass self. Wike (2014) noted that self-esteem relates closely with identity development and self-concept, in which the importance of the looking-glass self has been highlighted. The looking-glass self is where one imagines how others regard and judge them, directly influencing their selffeelings.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, prolonged exposure to public pressure and stress has placed homosexuals in a poorer state of psychological well-being such as lower self-esteem, and has caused them to suffer more mental health problems, including suicide (Blosnich, Nasuti, Mays, & Cochran, 2016;Graybill & Proctor, 2016). Not surprisingly, homosexuals tend to have lower self-esteem than their heterosexual counterparts (Pachankis & Goldfried, 2006), whereas other studies have revealed that low self-esteem drives maladaptive coping strategies which can explain homosexuals' suicidality (Purvis, 2017;Wike, 2014). Sexual minorities are at risk for higher prevalence of suicide; as noted by Heeringan and Vincke (2000), these individuals have a twofold increase in the risk of suicidal ideation because of their sexual orientation.…”
Section: Introductionmentioning
confidence: 99%
“…This population will also become increasingly diverse as nearly 40% of all older adults will belong to racial and ethnic minoritized groups by 2050, up from barely 20% in 2012 [ 1 ]. Hence, a larger and more diverse group of Americans may face unique challenges presented by aging such as changes to income and financial burden [ 2 ], decisions regarding housing and living arrangements [ 3 ], and changes in social networks and social activities [ 4 ]. Older adults who are racial minorities [ 5 ] may be at higher risk of experiencing these challenges as they are more likely to occupy multiple minoritized statuses, such as being African American, having advanced age, and lower income; and to encounter negative experiences such as discrimination associated with these statuses [ 6 ].…”
Section: Introductionmentioning
confidence: 99%